Fluorescence energy transfer in the rapid-diffusion limit - Thomas, David D. (Proc Natl Acad Sci U S A, 1978)
Energy transfer is enhanced by translational diffusion of the donor and acceptor [Steinberg, I. Z. & Katchalski, E. (1968) J. Chem. Phys. 48, 2404-2410]. The effect of diffusion on energy transfer depends on Dτ(0)/s(2), in which D is the sum of the diffusion coefficients of the donor and acceptor, τ(0) is the lifetime of the donor in the absence of transfer, and s is the mean distance between donors and acceptors. In most previous studies, Dτ(0)/s(2) ≪ 1, corresponding to the static limit. We report here steady-state and kinetic fluorescence experiments showing that Dτ(0)/s(2) ≫ 1, the rapid-diffusion limit, can be attained by using Tb(3+) chelated to dipicolinate as a long-lived energy donor (τ(0) = 2.2 msec). The concentration of rhodamine B, the energy acceptor, resulting in 50% transfer was 0.67 μM, which is three orders of magnitude less than the concentration giving 50% transfer in the static limit. The dependence of the transfer efficiency on diffusion coefficients varying from 5 × 10(-11) to 1.5 × 10(-4) cm(2)/sec, spanning the range from the static limit to the rapid-diffusion limit, is in excellent agreement with theory. It is evident that energy donors with millisecond or longer excited state lifetimes can be used to probe translational motions in membranes and other assemblies. Energy transfer in the rapid diffusion limit is sensitive to the distance of closest approach (a) of the donor and acceptor. For a Tb·(DPA)(3) chelate trapped inside the aqueous space of a membrane vesicle containing eosin phosphatidylethanolamine, a = 10 Å. The transverse location of chromophores in model membranes and biological membranes can be determined by this technique.